Principle of Educational Management in Hybrid Learning - JIA, XIONG; Fernando, Yudi (PT. BERBAGI TEKNOLOGI SEMESTA, 2024)
Hybrid learning occasioned by the introduction of the traditional face to face instruction with online learning mechanisms, has developed as a prominent educational approach in response to the developing landscape of teaching and process of learning. The professional management of hybrid learning ecosystems is important for ensuring best students’ engagement, the outcomes of learning, and the general success. The study investigates the principles of educational management of hybrid learning environments highlighting basic consideration and methods for the management. Based on the established principles of educational management, such as effective communication, support system, assessment and curriculum patterns, this study investigates how these principles apply in the realm of hybrid learning. In addition to that, the study explores the contribution of technology in helping management processes and improving student experiences in hybrid environments. Understanding and adopting the tenants of educational management in hybrid learning setups, educators can come up with dynamic, inclusive, and effective learning experiences that satisfies the diverse demands of the students and promote academic excellence